The Role of Ornaments for the Gedhe Kauman Mosque - Taufan Hidayatullah; Rifa Nur Fadhilah (ARTic, 2022)
This study aims to describe the role of the ornaments found in the Gedhe Kauman Mosque by having various forms with different meanings. The Gedhe Kauman Mosque building is a place of worship whose history is still attached to the local community, especially in Yogyakarta. The Gedhe Kauman Mosque was built during the Sultanate of Hamengku Buwono with an architect Ki Wiyukusumo with the aim of forming an Islamic state which at that time, the city of Yogyakarta was still in the process of Islamization and the spread of Islam was still being moved. This research is descriptive qualitative by discussing some of the history of the Gedhe Kauman Mosque building as well as some parts of the ornaments printed on the Gedhe Kauman Mosque building. The research data was obtained by means of literature study, observation, documentation and interviews with sources who know about the Gedhe Kauman Mosque building and its contents. There are several ornaments that will be discussed with each having a different meaning. The conclusion of this study is to add insight into works of art that are applied to buildings of worship with a very important meaning in them. Keywords: Art and Ornament Mosque; Design; Islam; Moslem; Yogyakarta Indonesia